Pengembangan Kurikulum Diklat Budidaya Lebah (Trigonula sp.) untuk SMA, Mahasiswa, dan Umum - Utami, Sri; Sulistyarsi, Ani; Winarsih, Eni; Widiyanto, Joko; Atmojo, Frihatnolo Pardani (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2024)
Universitas PGRI Madiun has provided assistance to MSMEs An-Nahl Madiun Group since 2020 until now. These assistance activities include hygienic packaging of beekeeping products, online and offline marketing. The impact of this assistance has made CV. An-Nahl Group is more advanced and known in the East Java region and throughout Indonesia. There are many visitors who want to learn about beekeeping from all walks of life, whether from the general public or an agency. Based on request from CV. An Nahl Madiun Group, the research team developed a bee cultivation training curriculum for high school students, students and the general public. This research is Research and Development (R&D) research using the Borg and Gall development model developed by Sugiyono (2016). There are 10 stages of R&D, namely potential problems, data collection, product design, design validation, design revision, product trials, product revisions, use trials, final stage product revisions, and mass production. This research adopts 8 R&D steps according to Sugiyono. The development steps we take include: 1) potential and problems; 2) data collection; 3) product design; 4) design validation; 5) design revision; 6) product testing; 7) product revision; and 8) limited production. The results of data validation analysis show a curriculum validity level of 83.65% (Quite Valid), with a feasibility level of